ANALISA TEGANGAN POROS MOBIL LISTRIK TARSIUS X3 MENGGUNAKAN SOFTWARE - Firlya Rosa; Joko Mardi Utomo (Jurnal Turbulen, 2019)
The development of the automotive industri in Indonesia that uses electrical energy sources is still a competition in the environment of college students. One of them is the Tarsius X3 electric car that has 2 kilowatts of power with a rear drive system that is used to transfer power from the electric motor to the wheels. Development, design and analysis of the drive shaft using software, aims to determine the surface tension and deformation that occurs on the shaft. Stress analysis uses the theory of energy distortion (von mises). Loading on the shaft is based on, electrical motor torsion, the weighing of car and stress of the shaft material permits by conducting tensile testing of the ASTM E-8 method as input for simulating CAD software (Inventor). The software simulation results show that the von mises maximum stress occurs at 162.463 MPa and the minimum stress occurs at 0.0011 MPa. The maximum deformation occurs at4.74 x 10-2mm and a minimum of 0 mm. The stress and deformation that occur is still at the safety factor limit of 3.83 at under static conditions. Keywords: Shaft, Von Mises Stress, Safety Factor, Deformation